A Systematic Review: Strategies in Chemistry Learning - Sari, Winda Putri Permata; Atun, Sri (Department of Chemistry Education, UIN Sunan Gunung Djati Bandung, 2025)
This study aims to synthesize research related to learning strategies focusing on chemistry learning research in the last ten years from various reputable journals and proceedings focusing on the last ten years, grounded in the theoretical framework of conceptual change and the challenges posed by chemistry's multiple representational levels (macroscopic, submicroscopic, and symbolic). After searching national and international reputable databases using key patterns of relevance (Pattern 1: “chemistry learning strategies” “Merdeka Curriculum”; Pattern 2: “learning strategies” ‘chemistry education’; Pattern 3: ‘chemistry learning strategies’ ‘effective’), the 19 relevant articles were systematically reviewed. Inclusion criteria required publication in reputable journals (Q1–Q4) or proceedings, english language, and explicit discussion of strategy effectiveness in secondary or higher chemistry education. The results showed that cooperative learning and inquiry learning dominated from several articles used as learning that is often applied in the learning process to see its effect on learner achievement, cognitive development, laboratory skills, science process skills, and understanding of science knowledge. The implementation of the Merdeka Curriculum requires educators to provide innovations to the learning strategies applied. Technology-based learning is one form of innovation that is in accordance with the curriculum and the development of the current era. Learning strategies by utilizing ICT create enthusiasm and meaningfulness for students to learn independently. This review contributes a refined theoretical understanding of chemistry specific learning strategies, identifies research gaps, and suggests future directions in chemistry education.